Direct cash assistance on the development and sustainability of micro small enterprises in Bandung regency, Indonesia - Soemaryani, Imas; Kaltum, Umi; Kurniawan, Meinanda; Triski, Dara Sagita (International Journal of Management and Sustainability, 2025)
The COVID-19 pandemic has significantly affected micro, small, and medium-sized enterprises (MSMEs), causing revenue losses, business closures, and workforce reductions compounded by supply chain disruptions. Governments have introduced direct cash assistance (DCA) programs such as Indonesia's Productive Presidential Assistance for micro enterprises to support 12 million MSMEs, particularly those excluded from bank loans or certain sectors. This program seeks to sustain operations, restore purchasing power, and alleviate long-term pandemic impacts. Despite its objectives, challenges remain, including coordination issues among implementing agencies and ineligible MSMEs registering for assistance. Additionally, fluctuating fund allocations had varying effects on businesses, highlighting the need for program optimization. The research, conducted in Bandung Regency, reveals that while millions of MSMEs have benefited from the aid, its direct impact on business sustainability varies between 10% and 50%, with funds primarily spent on essential business needs. The study emphasizes the importance of government cash assistance in supporting MSMEs during crises. It contributes to the literature by examining the role of DCA in promoting MSME sustainability and development, particularly during a pandemic. Theoretical implications suggest that DCA is a form of social protection aligning with government compensation for societal welfare. Further research is needed to optimize DCA utilization for fostering MSME growth and resilience, especially in the post-pandemic era.